The role of educational process dimensions in improving open innovation / An Exploratory study of the opinions of a sample of workers in the College of Information Technology / University of Nineveh (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2025)
The study aimed to know the role of the dimensions of the educational process in improving open innovation in the College of Information Technology as the applied field of the study, where the survey method was used for a group of workers in the college of the study sample, where the number of questionnaire forms distributed to the workers reached (50) forms prepared for the purpose of collecting and analyzing them, and the study concluded that there is a statistically significant relationship between the educational process and open innovation for the staff working in the college of the study sample. The results of the study showed that all dimensions of the educational process were different, as the dimensions of training and software practice were at a very good degree, followed by the practice of computer programs and networks - communications at a good degree, and the open innovation variable was at a good degree. Based on the conclusions reached by the study, a set of recommendations were presented, the most important of which is the necessity of the college of the study sample using open innovation in communicating with other educational colleges at home and abroad to keep pace with modern educational technology.